Urban noise mapping: the impact of traffic noise level in the environmental noise pollution - Maja Anachkova, Simona Domazetovska, Petreski Zlatko, Viktor Gavriloski (My University, 2020)
The European Union proposes noise protection measures adopted in accordance with European legislation, emphasizing environmental noise pollution as an important environmental problem. The legislation imposes European Directive 2002/49/EC, which aims to establish a common basis for addressing noise problems in Europe through noise maps which are a powerful tool for controlling the population exposure to environmental noise. In this paper, a noise map generation based on using the vehicle flows on four boulevards that enclose a living area in the center of Skopje, the capital city of North Macedonia is described. For this purpose, statistics on the flow of vehicles on the boulevards are provided by Traffic Management and Control Center. The noise simulations were created using a noise propagation model in IMMI as simulation software. The initial map was additionally validated by performing short-term measurements at the intersections of these boulevards in order to come to a conclusion of the impact of the traffic noise pollution in the overall environmental noise situation. The advantage of having this map representation of traffic noise allows for a more accurate view of the actual environmental noise circumstanes in the city center, determining more quickly the causes of high noise levels and, consequently, any mitigation action required.
Keywords: urban noise mapping, traffic noise pollution, noise exposure